Balanço energético e seletividade alimentar de Hyphessobrycon eques e Serrapinnus notomelas (Pisces, Characiformes) - Matheus, Fábio Eduardo (2006)
The trophic ecology and bioenergetic aspects of most small fishes were not yet investigated, although they are important components in the ictiofauna, largely contributing to the richness of species and to the energy flow in aquatic ecosystems. The energy budgets and the food selectivity of two species of small fishes, Hyphessobrycon eques and Serrapinnus notomelas, were analysed. Natural populations were sampled from Monjolinho River, São Carlos, SP, in the period between September to December 2005, and January to April 2006. Food selectivity experiments and energy budgets experiments were performed in the laboratory using planktonic and benthic invertebrates as food items. Food selection was evaluated by Paloheimo index, by calculating the normalized forage ratio. Both species had preference and positive selection for the dipteran larvae Aedes aegypti, Chironomus xanthus and Chaoborus sp., as well as for the cladocerans Daphnia laevis and Ceriodaphnia silvestrii. They presented negative selection or absence of selection for Hyalella meinerti and Cypricercus mucronata. The positive selection of both species of fishes for the larvae of Aedes aegypti evidenced that they have potential to be used in the biological control on dengue disease epidemies. The results obtained from the energy balances revealed that S. notomelas has higher consumption and assimilation rates than H. eques, however its production efficiency is lower as a consequence of higher metabolic expenditures. On average the production efficiency was 53% for H. eques and 22% for S. notomelas. The values obtained for the instantaneous net production efficiency of both species were higher than those reported in the literature for carnivorous fishes (20%) and also higher than those reported for natural populations of small fishes in tropical regions.